VALUE-MOTIVATIONAL SPHERE OF THE DEVIANT PEOPLE AND PSYCHOTHERAPY OF EDUCATIONAL RELATIONSHIPS - Tyumaseva, Z.I.; Valeeva, G.V.; Nasyrova, E.F.; Krasnoshchechenko, I.P.; Yusipova, I.V.; Khudyakova, T.L.; Kassymova, G.K.; Arpentieva, M.R. (Scientific Journal of Pedagogy and Economics, 2020)
The objective of this article is to analyze the problems of deviant behavior in the context of the processes. The method of research is a theoretical analysis of the problem of deviant behavior in the context of the processes and results of deformations of the value system of an individual and the community. Results. Deviations in human behavior in different ages are manifested in a variety of forms, such as aggression and autoaggression, alcoholism and drug addiction, offenses and crimes, and new forms of the addiction. The problem of the (re/trans) formation of a system of values is touched upon in the multitude of works by modern and classic scientists, pedagogues, social workers, and other specialists. Production-technological, socio-psychological and politico-economic changes in worlds have led to the destruction and desacralization of the customary system of values, such as moral norms, their representation in interaction with fatherland, family and friendship, professional and work communication. Modern societies began to exist in the spirit of principles and rules of life, that values are formed spontaneously and exists in individual forms. This makes these norms very vulnerable to deviations and crushes the very understanding of deviations. Conclusions. In working with deviations in the framework of academic psychological counseling and psychotherapy of educational disorders (didactogeny), it is important to understand that value deformations are not only a person and their relationships, but also the social context, including state and national programs and deformations. Therefore, work with violations is related to helping a person to remain human or to help restore human status in the foot despite the circumstances, anomie, and desacralization of macro-social crises and injuries.